Brumadinho Dam InSAR study: analysis of TerraSAR-X, COSMO-SkyMed and Sentinel-1 images preceding the collapse - Holden, D; Donegan, S; Pon, A (Slope Stability 2020: 2020 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2020)
The catastrophic failure of Dam I at the Córrego do Feijão iron ore mine near Brumadinho, Brazil has brought significant attention to the range of monitoring techniques available for similar sites, including satellite Interferometric Synthetic Aperture Radar (InSAR). Satellite InSAR is a remote sensing technique that uses satellite imagery to detect millimetre scale displacements. This paper presents InSAR results covering the Brumadinho site, for the time period leading up to the dam collapse, using both high and low resolution imagery from four sets of satellite synthetic aperture radar (SAR) data. The goal of this study is to provide a set of results that may help to improve the understanding of the mechanisms behind the collapse and to understand if there was a role that InSAR could have played in detecting any anomalous displacement signals before the collapse. Four sets of satellite SAR images are available and have been analysed in this study. These include two from the Sentinel-1 (S1) satellite constellation, which have a lower resolution (20 m), and two from the higher resolution (3 m) TerraSAR-X (TSX) and COSMO-SkyMed (CSK) satellite constellations. The high resolution CSK and TSX measurements also provide a much greater level of detail on the dam that can be used to distinguish local trends. Some subtle signals are observed on the lower portion of the dam wall in the year leading up to the collapse, however, these are not statistically significant based solely on the level of noise present in the InSAR results. At the top of the wall and inside of the enclosure, significant signal is present, as expected for a structure of this type.
Keywords: InSAR; Brumadinho; tailings; dam; failure; collapse; Córrego do Feijão